2016
DOI: 10.1002/hep.28396
|View full text |Cite
|
Sign up to set email alerts
|

Terlipressin given by continuous intravenous infusion versus intravenous boluses in the treatment of hepatorenal syndrome: A randomized controlled study

Abstract: In patients with cirrhosis and hepatorenal syndrome (HRS), terlipressin has been used either as continuous intravenous infusion or as intravenous boluses. To date, these two approaches have never been compared. The goal of this study was to compare the administration of terlipressin as continuous intravenous infusion versus intravenous boluses in the treatment of type 1 HRS. Seventy-eight patients were randomly assigned to receive either continuous intravenous infusion (TERLI-INF group) at the initial dose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
208
0
13

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(225 citation statements)
references
References 23 publications
4
208
0
13
Order By: Relevance
“…This letter regards the recently published article by Cavallin et al (1) The authors compared terlipressin given by continuous intravenous infusion (TERLI-INF) and by intravenous boluses for hepatorenal syndrome and concluded that TERLI-INF is the most suitable approach because it was safer and required lower doses.…”
Section: To the Editormentioning
confidence: 90%
“…This letter regards the recently published article by Cavallin et al (1) The authors compared terlipressin given by continuous intravenous infusion (TERLI-INF) and by intravenous boluses for hepatorenal syndrome and concluded that TERLI-INF is the most suitable approach because it was safer and required lower doses.…”
Section: To the Editormentioning
confidence: 90%
“…In two cases, continuous perfusion was used with 9 and 12 mg/day respectively. A recently published study (10) suggests that continuous infusion could avoid secondary effects, as lower doses of the drug are needed. However, none of the patients within this study presented with cutaneous necrosis; they only report one isolated peripheral ischemia case within the continuous infusion group.…”
Section: Discussionmentioning
confidence: 99%
“…[23] The adverse effects of terlipressin may be minimized by means of intravenous infusion rather than bolus injections as shown in a recent randomized controlled study in Italy. [24] Although most commonly used and studied, terlipressin is expensive and unavailable in many countries. Other vasoconstrictive agents are used as well.…”
Section: Strategies To Bridge To Liver Transplantationmentioning
confidence: 99%